Representation of Social Criticism in the Documentary Film Netflix: Miss Americana - Irfan Hadi; Nia Liska Saputri (International Journal of Education, Information Technology, and Others, 2020)
This study aims to describe the representation of social criticism in the documentary film Netflix: Miss Americana (2020) by using John Fiske's Semiotic analysis technique. Based on the research finding, the writer concludes that there are social criticism representations in documentary film Netflix: Miss Americana seen from media interviews and entertainment reality shows. Through the whole interviews and arguments, Taylor Swift explained in the movies that she needs to be on the right side of history especially through political views. She also mentioned in Miss Americana that she doesn’t want any other else’s input about her body and others' criticism to impact her life anymore. Furthermore, this documentary film also says that speaking up against what isn't right is a necessity, especially if we are young and we are a woman. "Miss Americana" offers an effective backstage look at Taylor Swift that works best when the megastar opens up about her life